2001
DOI: 10.1074/jbc.m106282200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Vascular Endothelial Growth Factor Expression and Hypoxia-inducible Factor 1α Protein by the Oxidative Stressor Arsenite

Abstract: Recent evidence suggests that vascular endothelial growth factor (VEGF) expression is up-regulated by oxidative stressors through activation of hypoxia-inducible Factor 1 (HIF-1). To investigate whether this is a general phenomenon, we studied the effects of the sulfhydryl reagent arsenite on VEGF expression in human ovarian cancer cells. Arsenite potently induces the production of reactive oxygen species (ROS) in several cell systems and directly interacts with sulfhydryl groups of cellular thiols. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 64 publications
7
90
0
Order By: Relevance
“…Hybridization of total RNA to a 136-nucleotide human ␥-actin antisense probe gives rise to a protected fragment of 130 nucleotide, whereas hybridization to the 185-nucleotide murine ␥-actin antisense probe is expected to result in the protection of a fragment of 151 nucleotides. It should be noted that hybridization of total RNA to the 301-nucleotide human VEGF 165 antisense probe and the 228-nucleotide murine VEGF 164 can give rise to fragments of different sizes because of protection by VEGF mRNAs of different isoforms (1,34,41,42). Protection by human VEGF 165 mRNA and murine VEGF 164 mRNA is most efficient, giving rise to protected fragments of 252 and 195 nucleotides, respectively.…”
Section: And Hif-1␣mentioning
confidence: 99%
See 4 more Smart Citations
“…Hybridization of total RNA to a 136-nucleotide human ␥-actin antisense probe gives rise to a protected fragment of 130 nucleotide, whereas hybridization to the 185-nucleotide murine ␥-actin antisense probe is expected to result in the protection of a fragment of 151 nucleotides. It should be noted that hybridization of total RNA to the 301-nucleotide human VEGF 165 antisense probe and the 228-nucleotide murine VEGF 164 can give rise to fragments of different sizes because of protection by VEGF mRNAs of different isoforms (1,34,41,42). Protection by human VEGF 165 mRNA and murine VEGF 164 mRNA is most efficient, giving rise to protected fragments of 252 and 195 nucleotides, respectively.…”
Section: And Hif-1␣mentioning
confidence: 99%
“…In a previous study on the role of oxidative stress in the regulation of VEGF, we showed that sodium arsenite (NaAsO 2 ) induces HIF-1␣ protein and VEGF mRNA and protein levels in the human ovarian cancer cell lines OVCAR-3 and H134 (34). Arsenite induces oxidative stress by binding to thiol groups of cellular proteins and by increasing the production of ROS.…”
Section: Vasular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
See 3 more Smart Citations